2021
DOI: 10.1049/nbt2.12026
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of diabetic nephropathy by zinc oxide nanoparticles in streptozotocin‐induced type 1 diabetes in rats

Abstract: This study examines the effect of nanoparticles with zinc oxides (ZnONPs) on diabetic nephropathy, which is the primary cause of mortality for diabetic patients with end-stage renal disease. Diabetes in adult male rats was induced via intraperitoneal injection of streptozotocin. ZnONPs were intraperitoneally administered to diabetic rats daily for 7 weeks. Diabetes was associated with increases in blood glucose level, 24-h urinary albumin excretion rate, glomerular basement membrane thickness, renal oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Recently, ZnO NPs have been reported to supply therapeutic proportions in contrast to chemotherapy drugs and have a high degree of cancer cell selectivity [ 15 ]. Regardless of their method of synthesis, and because of their low toxicity and biodegradability, ZnO NPs have been used in the inhibition of UV radiation [ 16 ], antidiabetic activity [ 17 , 18 ], antimicrobial agent [ 19 ], anti-inflammatory agent [ 20 ], wound healing [ 21 ], cancer imaging and diagnosis [ 22 ], photocatalysis [ 16 ], electronics [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ZnO NPs have been reported to supply therapeutic proportions in contrast to chemotherapy drugs and have a high degree of cancer cell selectivity [ 15 ]. Regardless of their method of synthesis, and because of their low toxicity and biodegradability, ZnO NPs have been used in the inhibition of UV radiation [ 16 ], antidiabetic activity [ 17 , 18 ], antimicrobial agent [ 19 ], anti-inflammatory agent [ 20 ], wound healing [ 21 ], cancer imaging and diagnosis [ 22 ], photocatalysis [ 16 ], electronics [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our research examining the effect of zinc oxide NPs (ZnONPs) on diabetic nephropathy indicated that ZnONPs could ameliorate the renal damage induced in a diabetic rat model of nephropathy via improving renal functionality; inhibiting renal fibrosis, oxidative stress, inflammation and abnormal angiogenesis; and delaying the development of podocyte injury [102].…”
Section: Contribution Of Authors To the Nano-based Diabetes Therapymentioning
confidence: 99%
“… ZnONPs can improve renal function, by inhibiting renal fibrosis, oxidative stress, inflammation, and abnormal angiogenesis and the ameliorating podocyte injury to ameliorate the renal damage. Alomari et al 85 Cao et al 81 3.2 Nano-Composite Oxides MET-HMSN-CeO 2 NPs Cerium oxide and metformin Kidney Ceria with surface provide high oxygen storage abilities and can scavenge free radicals via the self-circulation of redox reaction and MET as glucose production inhibitor can inhibit glucose production. Combined antioxidative with antidiabetic activities, nanoparticle administration can exhibit specially nephroprotective ability without causing major side effects.…”
Section: Introductionsmentioning
confidence: 99%